2020
DOI: 10.1111/ceo.13821
|View full text |Cite
|
Sign up to set email alerts
|

Association between intraocular lens diopter and posterior capsular opacification

Abstract: Importance: Posterior capsular opacification (PCO) is the most common complication after cataract surgery. Background: We aimed to assess the relationship between intraocular lens (IOL) diopter and formation of PCO among a consecutive real-world registry. Design: Cohort study. Participants: Included were 14 264 consecutive cases of uncomplicated cataract surgery performed during 2014 to 2018 in Helsinki University Hospital in Finland. Methods: Nd:YAG capsulotomies were used as an estimate of clinically signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 19 publications
5
10
0
Order By: Relevance
“…It should be considered that the number of cases completing a follow-up of more than 7 years was reduced. This trend was consistent with the findings of other studies showing similar PCO progression rates [ 8 , 25 , 28 ]. Hecht and coauthors [ 8 ] showed for a specific model of hydrophobic IOL that the PCO rate increased from 1.1% at 1 year after surgery to 7.1% and 10.2% at 3 and 4 years, respectively.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…It should be considered that the number of cases completing a follow-up of more than 7 years was reduced. This trend was consistent with the findings of other studies showing similar PCO progression rates [ 8 , 25 , 28 ]. Hecht and coauthors [ 8 ] showed for a specific model of hydrophobic IOL that the PCO rate increased from 1.1% at 1 year after surgery to 7.1% and 10.2% at 3 and 4 years, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…This trend was consistent with the findings of other studies showing similar PCO progression rates [ 8 , 25 , 28 ]. Hecht and coauthors [ 8 ] showed for a specific model of hydrophobic IOL that the PCO rate increased from 1.1% at 1 year after surgery to 7.1% and 10.2% at 3 and 4 years, respectively. Praveen et al [ 28 ] reported a significant increase of PCO rate for a hydrophobic acrylic IOL during the first 3 years after surgery, with a more limited increase afterwards.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations